Figure S1 from PARP Inhibition Induces Synthetic Lethality and Adaptive Immunity in LKB1-Mutant Lung Cancer - Li-Li Long (14963775) (2025)
LKB1 deficiency impairs IFNγ pathway by hindering STAT1 phosphorylation. (a) Western blotting for detection of LKB1 and pAMPK expression in K and KL lung tumors. (b) UMAP of sub-clustered CD45+ immune cells from lung tumor samples of K and KL, colored by cell types. (c) The proportion of each immune cell type in K vs KL. (d) UMAP of sub-clustered cells from lung tumor samples of KP and KPL mice, colored by their 10 major cell types. (e) Gene set enrichment analysis (GSEA) showing downregulated response to interferon-gamma in KPL compared with KP. (f) A549 lung cancer cells were transfected with lentivirus expressing the indicated genes (LV-Ctrl, LV-LKB1-WT, and LV-LKB1-Mut) followed by stimulation with IFNγ. The expression of LKB1 and pAMPK was analyzed by western blotting. (g) Expression of pSTAT1 was measured by immunofluorescent staining in the three groups of A549 cells treated with IFNγ for 24 hours. Nuclei were visualized with DAPI (blue). Scale bar = 100 μm. (h) Immunoblot of the indicated IFNγ-induced proteins in different lung cancer cells. (i) Decreased IFNγ signaling downstream molecules, PD-L1, and chemokines, in KPL vs KP malignant cells. (j) PD-L1 transcription and chemokine signature score in tumor cells of K vs KL. (k) Western blot illustrating LKB1 expression in LLC1 and CMT-167 cells respectively. (l, m) Lewis lung cancer cells (LLC1) were transfected with shRNA specific for Lkb1 (shLkb1) or noneffective scrambled shRNA (shCtrl) followed by treatment with IFNγ for 24 hours. Western blotting for the detection of pSTAT1, STAT1, LKB1, and pAMPK expression was performed. (n) Flow cytometry analysis of cell surface PD-L1 of tumor cells from mice bearing LLC1-shLkb1 and LLC1-shCtrl tumors. (o) Tumors from mice bearing LLC1-shLkb1 and LLC1-shCtrl derived tumors were analyzed by Q-PCR for detecting CXCL9, CXCL10, CXCL11 and CCL5. (p) Representative IHC staining of CD8+ T cells and quantification of infiltrated CD8+ T cells in LLC-LV-Lkb1 tumors treated with indicated treatment (n=3 mice each group). Scale bar: 100 µm. n = 5 fields from independent tumors. Error bars represent mean ± SD. Statistical analyses were performed using unpaired t-tests. (****, P < 0.0001; ***, P < 0.001; **, P < 0.01; *, P < 0.05). (q) LLC1/LV-Ctrl or LLC1/LV-Lkb1 tumors were administered with different treatments, anti-PD-1 monotherapy or combination treatment (n=7 mice/group). Tumor size was monitored. Results are presented as mean ± SEM; * P < 0.05; two-way ANOVA.